The role of human resource practices for including persons with disabilities in the workforce: a systematic literature review. Issue 1 (17th January 2022) - Schloemer-Jarvis, Aileen; Bader, Benjamin; Böhm, Stephan A.
Abstract: Organizations are increasingly aware that a better vocational inclusion of persons with disabilities (PWD) is in their self-interest for reasons such as a shortage of skilled labor, an increasing prevalence of disability in their aging workforces, and changed societal attitudes and laws regarding the promotion of diversity and equity in the workplace. Human resource (HR) practices have been identified as a primary enabler of inclusion, yet research on disability-related HR Management is scattered across disciplines. To provide an evidence-based analysis and integration, this article systematically reviews the literature on HR management in the context of employing persons with disabilities, using the high-performance work practices 'selection and staffing', 'training and development', '(performance) appraisal, promotion, and career management' and 'compensation and benefits' as an organizing framework. We systematically reviewed and summarized the key findings of 74 empirical studies conducted from 1990 through 2020. Most studies focused on selection and staffing practices, providing strong evidence that standardization and structure reduce bias in the appraisal of PWD and related employment decisions. Research regarding appropriate HR practices that allow to utilize, develop and reward PWDs' potential, in contrast, is still in its infancy.